2020
DOI: 10.21203/rs.2.21028/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytocompatibility of 3D printed dental materials for temporary restorations on fibroblasts

Abstract: Background Three-dimensional (3D) printing is widely used in the fabrication of dental prostheses; however, the influence of dental materials used for 3D printing on temporary restoration of fibroblasts in tissues is unclear. Thus, the influence of different dental materials on fibroblasts were investigated. Methods Digital light processing (DLP) type 3D printing was used. Specimens in the control group were fabricated by mixing liquid and powder self-curing resin restoration materials. The temporary resin mat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Polished printable resins other than those tested in this study have been reported to have higher proliferation rates of L929 mouse cells than those for polished conventionally processed materials. 28 Attempts have been made to reduce the cytotoxic potential of printed materials, with postpolymerizing and rinsing in ethanol or isopropyl being reported to reduce the toxic effects of the printed materials, although the effect of rinsing depended on the material. 10,12,15,16 Most manufacturers recommend rinsing and postpolymerizing of printed parts.…”
Section: Discussionmentioning
confidence: 99%
“…Polished printable resins other than those tested in this study have been reported to have higher proliferation rates of L929 mouse cells than those for polished conventionally processed materials. 28 Attempts have been made to reduce the cytotoxic potential of printed materials, with postpolymerizing and rinsing in ethanol or isopropyl being reported to reduce the toxic effects of the printed materials, although the effect of rinsing depended on the material. 10,12,15,16 Most manufacturers recommend rinsing and postpolymerizing of printed parts.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages include, above all, the possibility of precise printing of restorations with complex shapes, as in the case of the CAD/CAM system, the elimination of polymerization shrinkage and thermal damage to the pulp, as well as greater biocompatibility compared to traditional selfcured materials. 35,36 The materials are available P.A. Łasica i inni www.protetstomatol.pl fused filament fabrication-modelowanie ciekłym tworzywem termoplastycznym), SLS (selektywne spiekanie laserowe), SLM (selektywne spiekanie metali), JetModeling (modelowanie strumieniowe), DLP (digital light processing-utwardzanie żywicy światłem UV), SLA (stereolitografia) oraz LFS (odmiana stereolitografii o mniejszej plamce lasera).…”
Section: D Printingmentioning
confidence: 99%
“…Do zalet należy zaliczyć przede wszystkim możliwość precyzyjnego drukowania uzupełnień o skomplikowanych kształtach, podobnie jak w przypadku techniki CAD/CAM eliminację skurczu polimeryzacyjnego oraz termicznego uszkodzenia miazgi, a także większą biokompatybilność w stosunku do tradycyjnych materiałów chemoutwardzalnych. 35,36 Materiały występują w wielu odcieniach według kolornika Vita. 33 Dodatkowo Chaturvedi i wsp.…”
Section: D Printingunclassified
“…Polymers are the most used materials in the 3D printing industry due to their diversity and ease of application. In dentistry, the photoinitiated resins are the most commonly used material [27], however, due to residual monomer and photoinitiator, most photosensitive resin materials are cytotoxic, affecting cell survival and physiological functions, since monomer diffusion impairs gingival cell viability [25,28,29].…”
Section: Introductionmentioning
confidence: 99%